Photovoicing versus Protein Food Frequency Questionnaire: Differences and Similarities in Measuring the Protein Intake of Community-Dwelling Older Adults - Joost O. Linschooten; Marije H. Verwijs; Marian A. E. de van der Schueren; Annet J. C. Roodenburg (Proceedings)
Research has shown that approximately 50% of Dutch older adults have a protein intake < 1.0 g/kg bw/day, and new strategies to improve protein intake have been suggested. Information on protein consumption can be collected via FFQs such as the Protein Screener 55+, but recent outcomes have shown that older adults may be incapable of estimating their own dietary intake. The aim of this study was to compare the reported intake in the Pro55+ with an estimate of protein intake based on photos taken over a period of 7 days to identify how accurate elderly people are in estimating their habitual protein intake over a period of 4 weeks. Protein intake was assessed in interviews using the food frequency questionnaire Pro55+, calculating the risk of a low protein intake (<1.0 gr/kg bw/day). The participants (n = 9) were asked to take photos of everything they consumed for a period of seven consecutive days and were asked whether they modified their consumption behaviour due to photographing. The reported frequency of consumption of products as categorized in the Pro55+ was compared with the frequency of foods visible in the photos as an indication for actual consumption. A Pro55+ score > 30% indicates a high risk of low protein intake (<1.0 gr/kg bw/day). The average Pro55+ score from the interviews was 44.9%, while the average photovoice-based Pro55+ score based on the observed data was 54.9%. In eight out of nine cases the participants overestimated the frequency of nuts/peanuts consumption as well as dairy products like yoghurt (six out of nine). On the contrary, consumption of eggs was underestimated by six out of nine participants. The Pro55+ is a validated screening tool for the risk of a low protein intake based on the consumption of specific groups of food items that have shown to have the highest predictive value. However, this easy-to-use tool depends on the self-reported intake of these items by older adults. The comparison of the reported intakes with the photos of meals and food products showed that it appeared to be difficult for older adults to give accurate estimates, which may suggest that older adults are also insufficiently aware of necessary modifications to their current behaviour to adhere to dietary guidelines, such as an increased protein intake.